The impact of prenatal care on childbirth satisfaction (Research, Society and Development, 2022)
Preparation from prenatal care, with guidance on pregnancy, childbirth and the puerperium, can increase women's safety and satisfaction. Therefore, they are fundamental scientific evidence on care practice during labor aimed at empowerment and satisfaction. This study verified whether there is a relationship between prenatal care and postpartum women's satisfaction with labor. We conducted a cross-sectional questionnaire study. Were included 178 puerperal women that answered 19 questions regarding demographic characteristics, prenatal care and satisfaction with the labor. Descriptive statistics and regression models were performed to identify an association between satisfaction with labor and prenatal care. We found that the chances of showing high satisfaction with the services provided during the labor increase 4.6 times, and the chances of showing medium satisfaction increase 25.5 times related to low satisfaction. The level of education about the labor influences satisfaction, with dissipated mothers 11.5 times more likely to have high satisfaction and 6.3 times more likely to have medium satisfaction with the services during the labor. In addition, the chances of showing high satisfaction increase 6.8 times and the medium chances increase 38.3 times related to the low level of satisfaction with their labor. Finally, we conclude that the level of instruction provided during prenatal care and how to prepare for childbirth is associated with the satisfaction level with labor services. Thus, prenatal care is an essential predictor of labor perception.